Bio-based methods with potentials for application in wooden furniture industry : Biološke metode s potencijalom za primjenu u proizvodnji namještaja od drva - Hrovatin, Karin (Array, 2020)
Furniture market is shifting towards green and innovative products. The use of bio-based methods in wooden furniture industry presents a big potential for the development of materials with new characteristics, of unique furniture items, and can reduce the environmental impact. Bio-based methods can be used for wood protection and decoration, fibre board production, and development of new wooden materials, such as wood hybrids and functionalised wood. The bio-based methods, investigated for their potentials in wood industry, include the use of living organisms, natural products, and biomimicry. Despite ongoing developments there are still major drawbacks associated with many of these technologies: unreliability and inadequate efficiency of the methods, inadequate mechanical properties or dimensional stability of the final products, and high costs. Thus, further developments are needed. In this review, we present the existing and arising bio-based methods with potential in wooden furniture production. Furthermore, we shortly present their marketing potential.